Effect of bariatric surgery in the body burden of persistent and non-persistent pollutants: longitudinal study in a cohort of morbidly obese patients - Díaz-González, B. Vanessa; Ramos-Luzardo, Álvaro; Henríquez-Hernández, Luis Alberto; Serra-Majem, Lluis; Bautista-Castaño, Inmaculada; Acosta-Dacal, Andrea; Luzardo, Octavio P.; Hernández-García, Elisabeth; Cornejo-Torre, Judith; Hernández-Hernández, Juan Ramón; Fernández-Valerón, Pilar (Frontiers in Endocrinology, 2024)
Introduction: Obesity is a pathological state that involves the dysregulation of different metabolic pathways and adipose tissue cells, constituting a risk factor for the development of other diseases. Bariatric surgery is the most effective treatment. The study of the behavior of pollutants in situations of extreme weight loss can provide biomonitoring information and tools to manage diseases of environmental etiology. Aim: To determine the prevalence of serum persistent and non-persistent pollutants in obese patients subjected to bariatric surgery and analyze the impact of sociodemographic variables on these changes. Methods: GC-MS/MS and UHPLC-MS/MS were utilized to determine the detection rates and concentrations of 353 compounds, including persistent organic pollutants (POPs), pesticides, pharmaceuticals, and rodenticide, in serum samples of 59 obese patients before and after undergoing bariatric surgery. Results: Detection rates of p,p'-DDE, HCB, β-HCH, naphthalene, phenanthrene and PCB congeners 138, 153 and 180 significantly increased due to surgery-induced weight loss. Serum levels of p,p'-DDE, PCB-138, PCB-153 and PCB-180 also increased after surgery. Correlations between naphthalene levels, weight loss, variation of total lipids and time after surgery were found. Additionally, correlations were observed between concentrations of PCB-138 and weight loss, and between phenanthrene levels and reduction of total lipids. No statistically significant differences were observed for other groups of contaminants, pharmaceuticals and other chemicals included in the quantification methods. Conclusions: Increment of POPs was observed after bariatric surgery. Serum concentrations of POPs after surgery were influenced by adiposity-related variables. Although biomonitoring studies show a decreasing tendency of exposure, rapid weight loss leads to an increase of circulating POPs. Further research on the interplay between adipose tissue, POPs and peripheral organs is required.